A limit on the mass of the ντ - Ammar, R; Baringer, P; Bean, A; Besson, D; Coppage, D; Darling, C; Davis, R; Kotov, S; Kravchenko, I; Kwak, N; Zhou, L; Anderson, S; et al. (1998)
A limit on the mass of the tau neutrino mντ is derived from 4.5 × 106 tau pairs produced in an integrated luminosity of 5.0 fb-1 of e+e- → γ * → τ+τ- reactions at center of mass energies ≈ 10.6 GeV. The measurement technique involves a two-dimensional extended likelihood analysis, including the dependence of the end-point population on mντ, and allows for the first time an explicit background contribution. We use the the decays τ → 5πντ and τ → 3π2π0ντ to obtain an upper limit of 30 MeV/c2 at 95% C.L. © 1998 Elsevier Science B.V. All rights reserved.